2014
DOI: 10.5430/jnep.v5n2p26
|View full text |Cite
|
Sign up to set email alerts
|

Teaching spirituality to student nurses

Abstract: Since Florence Nightingale, spiritual care has been embraced in professional nursing as the integration and promotion of purpose and meaning in life. Research reports that nurses have a prominent regard for spiritual care and acknowledge that it is part of their role. The intention of this literature review is to explore effective ways for nursing faculty to teach spiritual care. This in turn will help to advance spiritually educated nurses who can rise above obstacles to providing spiritual care to clients. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 49 publications
(72 reference statements)
3
13
0
5
Order By: Relevance
“…These assessment strategies included: (1) portfolio of evidence, (2) assignment, (3) questionnaire, and (4) observational standardized practical evaluation. These results are consistent with those of Bennett and Thompson (2015), who suggested that elements of spirituality could be incorporated in assignments where students practice spiritual assessment in a safe and conducive environment.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These assessment strategies included: (1) portfolio of evidence, (2) assignment, (3) questionnaire, and (4) observational standardized practical evaluation. These results are consistent with those of Bennett and Thompson (2015), who suggested that elements of spirituality could be incorporated in assignments where students practice spiritual assessment in a safe and conducive environment.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, self-reflection was considered as one of the important strategies in the educational guidelines. The teaching and learning strategies identified in the current study are consistent with those of previous studies that acknowledged drama, role playing, case study and discussion, searching databases and research analysis, self-reflection exercises, journaling, tutorial supervision, oral presentation about spirituality, group dynamics, and film and text analysis (Baldacchino, 2015;Bennett & Thompson, 2015;Caldeira et al, 2016;Mthembu et al, 2016). Additionally, Baldacchino (2015) described conceptual models, which may enhance learning about spirituality and spiritual care, such as Kolb's (1984) experiential learning theory, Gibbs' (1988) theory of reflective learning, and the ASSET model for Actioning Spirituality and Spiritual Care Education and Training in nursing (Narayanasamy, 1999).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations